2008
DOI: 10.1002/chin.200841263
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Dendrimers and Their Pharmaceutical Applications

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Shukla et al [88] demonstrated the FR-targeted boronated dendrimers as potential agents for neutron capture therapy. In addition, Singh et al reported that folate-PEG-dendrimer conjugate was significantly safe and effective in tumor targeting for 5-fluorouracil, compared to a non-PEGylated formulation [89]. Regarding ODN delivery using dendrimer, Wang et al revealed that dendrimer complex with VEGF-ASODN could prevent dendrimer (G4) from binding to the erythrocytes and bovine serum albumin and remained stable as a conjugate, therefore the toxicity of the complex was reduced [90].…”
Section: Folate-appended α-Cdes As Sirna Carriersmentioning
confidence: 99%
“…Shukla et al [88] demonstrated the FR-targeted boronated dendrimers as potential agents for neutron capture therapy. In addition, Singh et al reported that folate-PEG-dendrimer conjugate was significantly safe and effective in tumor targeting for 5-fluorouracil, compared to a non-PEGylated formulation [89]. Regarding ODN delivery using dendrimer, Wang et al revealed that dendrimer complex with VEGF-ASODN could prevent dendrimer (G4) from binding to the erythrocytes and bovine serum albumin and remained stable as a conjugate, therefore the toxicity of the complex was reduced [90].…”
Section: Folate-appended α-Cdes As Sirna Carriersmentioning
confidence: 99%
“…Due to the highly branched globular structure of dendrimers, they are attractive scaffolds for a wide variety of high-end applications, such as liquid crystals, [7] diagnostics, [8] solar cells, [9] sensors, [10] gene-transfection agents, [11] drug-delivery systems, [12] coating agents, [13] additives in commodity plastics, [14] and potential drugs. [15] Moreover, they have been successfully employed in a wide variety of catalytic reactions [17] as alternatives to insoluble [a] Organische Chemie, Technische Universität Dortmund, Otto-Hahn-Str. 6, 44227 Dortmund, Germany Fax: +49-231-755-5363 E-mail: peter.eilbracht@udo.edu-mail Supporting information for this article is available on the WWW under http://dx.doi.org/10.1002/ejoc.201001307 or from the author.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The research on dendrimer–drug interactions is an increasingly active area of research in biomedical sciences and pharmaceutical industry. 9,10,11,12 Using dendrimers as carriers 13 to target drugs to specific sites may make it possible to reduce the dosage or increase the efficiency of these drugs. Additionally, dendrimers could allow, in extreme chemical conditions, the transport of otherwise insoluble or reactive molecules, and ensure their safe delivery to the targeted location.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,14 The detailed understanding of dendrimer–drug interactions will help to establish the basis for developing novel dendrimer polymer chemistry applications in the field of biomedical sciences. 2,9,10,11 …”
Section: Introductionmentioning
confidence: 99%